Molecular Docking of a Bio Material [1-{[(Z)-Cyclopentylidene] Amino}-3-Phenylthiourea] by First Principles Study. (14th September 2021) - Pandey, Anoop Kumar; Shukla, D. V.; Singh, Prashant; Dwivedi, Apoorva
Abstract: Molecular Docking and complete quantum chemical studies of 1-{[(Z)-Cyclopentylidene] amino}-3-phenylthiourea have been done by using DFT/ B3LYP method and 6-311 G (d, p) as the basis set. We have compared optimized geometry of title molecule with experimental data. A detailed interpretation of the vibrational assignments of title molecule is reported. Molecular Electrostatic Potential (MESP) generated by a chemical species is widely used as a tool for exploring its properties and locating potential sites for interaction with other moieties. Nonlinear optics (NLO) is the branch of optics that describes the behavior of materials in nonlinear media. In quantum chemistry, a natural bond orbital or NBO is a calculated bonding orbital with maximum electron density. Time-dependent density functional theory (TDDFT) is a quantum mechanical theory used in physics and chemistry to investigate the properties and dynamics of many-body systems in the presence of time-dependent potentials, such as electric or magnetic fields.The electronic properties of title molecule are discussed with help of molecular FHOMO, FLUMO composition, band gap, and MESP plots. The NLO, NBO, UV spectra of title molecule also calculated with same level of theory. Some biological parameter Log P and Log S are also calculated which suggests that the title molecule have good ability to deliver drugs in various diseases.